Embodying scenes of moral disorder: Bodily gestures as a site of signification in feminist TikTok activism - Sigurdardottir Heba; Rautajoki Hanna (Nordic Journal of Media Studies)
Platformisation has facilitated the emergence of new rhetorical spaces where activists can creatively structure and present their political statements according to medium-specific affordances. In this article, we examine a group of activists on TikTok who topicalise gender-based violence and gender inequality through multimodal means of communication in short videos. We approached these videos as rhetorical arenas for communicating compelling messages with the aim of appealing to the audience. We used digital ethnography, multimodal discourse analysis, and approaches to the mediality of the body to conduct our investigation and analyses. Our results explicate how affective cues and bodily signals are put to rhetorical and political use in TikTok stories to pursue social change. That is, bodily performances stage interrelational positionings in a visual format, conveying affective evaluations and judgements about the state of the world and forming rhizomatic threads of messages to mobilise support and to affirm identification among the members of the movement.